The last stage in the life history of the European conger eel Conger conger: a transformation before death. Issue 2 (15th December 2019) - Battaglia, Pietro; Smith, David; Ammendolia, Giovanni; Cavallaro, Mauro; Maggio, Teresa; Consoli, Pierpaolo; Guerrera, Maria C.; Andaloro, Franco; Romeo, Teresa
Abstract: The taxonomic, morphological and meristic features of a dark eel caught by commercial trawling off the Gulf of Patti, southern Tyrrhenian Sea, Mediterranean Sea, February 17, 2017, showed it to be a female Conger conger . Histological analysis of gonads demonstrated that the individual was in a post‐spawning phase. X‐ray radiographs showed widespread decalcification of skeleton and teeth loss, confirming a strong mobilisation of somatic energy reserves needed for reproductive development.